Degradation of methylene blue using pillared TiO2 on de-oiled spent bleaching clay. (April 2018) - Hindryawati, N; Panggabean, A S; Fadillah, N D; Erwin,; Daniel,
Abstract: Degradation of methylene blue (MB) using pillared TiO2 onto spent bleaching clay has been conducted. Activation of deoiled spent bleaching clay (DSBC) has been done using acid, followed by pillarization with TiO2 using rarasaponin from Klerak fruit as surfactant. From the X-ray diffraction results show the mineral on DSBC is rectorite with dioctahedral mica layer and dioctahedral smectite with ratio 2:1. This molecule have formula Na.Al4 (Si, Al)8 .O20 .(OH)4 . H2 O and after calcinations the pattern TiO2 was appearance at 2θ: 27.4460°, 36.0850°, 54.3216° and 56.6403°. In order to test the catalytic performance of Ti-DSBC for photodegradation of MB under UV light was conducted under several reaction conditions. The highest degradation of MB was 90 % within 50 minutes and Ti-DSBC can be reused until 5 cycles with percent degradation MB was 84 %.